1994
DOI: 10.1007/bf00863768
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific patterns of neuronal loss in the spinal ventral horn in amyotrophic lateral sclerosis, multiple system atrophy and X-linked recessive bulbospinal neuronopathy, with special reference to the loss of small neurons in the intermediate zone

Abstract: The ventral horn cells of the fourth lumbar segment were morphometrically analysed in six cases of amyotrophic lateral sclerosis (ALS; there common forms and three pseudopolyneuritic forms), six of multiple system atrophy (MSA) with autonomic failure, four of X-linked recessive bulbospinal neuronopathy (X-BSNP), and seven age-matched autopsy cases of non-neurological disorders. In the common form of ALS, large and medium-sized neurons of the medial and lateral nuclei were markedly lost; small neurons in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 44 publications
2
47
1
Order By: Relevance
“…26 The pathology of this condition is that of ALS, with extensive myelinated fiber loss in the lateral corticospinal tracts of the thoracic and lumbar spinal cord segments. 27,28 We have shown in this study that the natural history of the FA and FL syndromes differs from more typical forms of ALS. The FA and FL syndromes have a significantly better prognosis in terms of median and 5-year survival rates compared to bulbar and limb onset ALS.…”
Section: Resultsmentioning
confidence: 60%
“…26 The pathology of this condition is that of ALS, with extensive myelinated fiber loss in the lateral corticospinal tracts of the thoracic and lumbar spinal cord segments. 27,28 We have shown in this study that the natural history of the FA and FL syndromes differs from more typical forms of ALS. The FA and FL syndromes have a significantly better prognosis in terms of median and 5-year survival rates compared to bulbar and limb onset ALS.…”
Section: Resultsmentioning
confidence: 60%
“…However, cases with pyramidal signs and absence of spinal cord pyramidal tract degeneration have been described (30,40). This clinicopathological dissociation may be accounted for by involvement of small neurons in the ventral spinal horn, which has been linked to spasticity and hyperreflexia in MSA (129). Although plantar extensor responses and hyperreflexia were common in this literature series, pyramidal weakness and spastic gait were rare, especially as presenting feature.…”
Section: Cerebellar Ataxia and Pyramidal Signsmentioning
confidence: 96%
“…Although moderate or severe degenerative change of the anterior horn cells was noted in 32% of 106 cases, subregional vulnerability was reported in only one study of six MSA cases. These authors found a marked reduction in small anterior horn neurons in the intermediate zone, whereas large and medium-sized neurons of the medial and lateral nuclei tended to be preserved (129).…”
Section: Pathological Featuresmentioning
confidence: 97%
“…The neuropathological basis of the nerve conduction abnormalities is most probably loss of large neurons in the ventral horn and reduction of myelinated sural nerve fibers [9, 10, 11, 12, 13]. The latter might be due to degeneration of dorsal root ganglion neurons.…”
Section: Discussionmentioning
confidence: 99%